"Ehrlich färbt am längsten". Sichtbarmachung bei Paul Ehrlich. Issue 4 (2nd December 2013) - Hüntelmann, Axel C.
Abstract: "Staining is the Best Policy". Visualization in the work of Paul Ehrlich. For nearly all of his life, the biomedical scientist Paul Ehrlich dedicated himself to work on dyes and staining at the interface between so‐called color‐chemistry and histopathology. The article begins by sketching out the field of histopathology at the junction of pathological anatomy, microtechniques, and the development of chemical dyes in the early 1870s when Ehrlich began his training as a medical student. The article explores Ehrlich's work staining first tissue and blood, and then pathogens and vital staining in the 1880s. In the late 1880s and 1890s, Ehrlich experimented with dyes as therapeutic agents. Staining made the invisible visible, revealing cell structures, pathogens, or vital physiological processes within the cell itself. The article shows how visualization became an essential – albeit laborious and painstaking – element in the epistemic process of Ehrlich's work. The production of histological specimens required special skills acquired through extensive practice, especially in the techniques of visualization, manipulation, observation, and tacit understanding. These practices were needed because it was increasingly necessary to produce objective results once the various techniques of visualization came to be assessed within a discourse on objectivity. Visualization itself became an epistemic object and was ultimately "more important than the subject matter itself".